Troponin elevation after percutaneous coronary intervention directly represents the extent of irreversible myocardial injury: insights from cardiovascular magnetic resonance imaging. - Selvanayagam, J; Porto, I; Channon, K; Petersen, SE; Francis, J; Neubauer, S; Banning, A (2005)
BACKGROUND: Although troponin elevation after percutaneous coronary intervention (PCI) is common, uncertainties remain about the mechanisms of its release and its relationship to the volume of myocardial tissue loss. Delayed-enhancement MRI of the heart has been shown to reliably quantify areas of irreversible myocardial injury. To investigate the quantitative relationship between irreversible injury and cardiac troponin release, we studied the incidence and extent of new irreversible injury in patients undergoing PCI and correlated it to postprocedural changes in cardiac troponin I. METHODS AND RESULTS: Fifty patients undergoing PCI were studied with preprocedural and postprocedural (24 hours) delayed-enhancement MRI for assessment of new irreversible myocardial injury. Cardiac troponin I measurements were obtained before PCI and 24 hours after PCI. Of these 50 patients, 24 underwent a further third MRI scan at a median of 8 months after the procedure. Mean patient age was 64+/-12 years. After the procedure, 14 patients (28%) had evidence of new myocardial hyperenhancement, with a mean mass of 6.0+/-5.8 g, or 5.0+/-4.8% of total left ventricular mass. All of these patients had raised troponin I levels (range 1.0 to 9.4 mug/L). Thirty-four patients (68%) had no elevated troponin I and no evidence of new myocardial necrosis on MRI. There was a strong correlation between the rise in troponin I measurements at 24 hours and mean mass of new myocardial hyperenhancement, both early (r=0.84; P<0.001) and late (r=0.71; P<0.001) after PCI, although there was a trend for a reduction in the size of PCI-induced myocardial injury in the late follow-up scan (P=0.07). CONCLUSIONS: In the setting of PCI, patients demonstrating postprocedural elevation in troponin I have evidence of new irreversible myocardial injury on delayed-enhancement MRI. The magnitude of this injury correlates directly with the extent of troponin elevation.